Writing Centres in Higher Education Working in and across the disciplines - Clarence, Sherran (African Sun Media, 2017)
This collection of essays reflects on the ways in which writing centres in South Africa are working in and across disciplines. Institutional constraints and challenges that arise from these collaborations are addressed and opportunities for transforming teaching and learning spaces are explored. The chapters speak to the global move in higher education to reconsider how knowledge is made, who makes it, and how support and development opportunities for students and lecturers should be created and sustained across the disciplines. This volume contributes to the body of knowledge in the growing field of the scholarship of teaching and learning in higher education in South Africa. It builds on the work of the first collection of such essays: Changing Spaces: Writing Centres and Access to Higher Education (Eds. A Archer and R Richards, 2011, SUN PReSS) to understand why working within the disciplines is so critical for writing development in a South African context.